FENOMENA SOSIAL REMAJA URBAN DALAM NOVEL MARMUT MERAH JAMBU: ANALISIS ISI DENGAN PENDEKATAN SOSIOLOGIS SASTRA - Luthfiah, Anisa Najwa; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
This research aims to explore and describe the social phenomena of urban adolescents represented in the novel Marmut Merah Jambu by Raditya Dika. The novel, categorized as humorous autobiographical fiction, has gained immense popularity among young readers. This study seeks to reveal the forms of representation of urban youth life, including lifestyle, communication patterns, and social dynamics presented in the novel. The research employs a qualitative approach through content analysis method, supported by a sociological literary approach as its theoretical foundation. Data are analyzed based on narrative observations, dialogues, and language use within the text. The findings reveal that the novel reflects the social realities of Indonesian urban youth, characterized by a consumerist lifestyle, digital communication, fluid romantic relationships, and identity struggles. These elements are conveyed through humorous and reflective narratives. The use of popular language and code-switching serves as a narrative strategy to construct an authentic urban youth atmosphere.